El silencio resistente: análisis de la desigualdad de las mujeres como autoras de contenido de opinión en la prensa local1 - Dra. Belén GALLETERO-CAMPOS,Dra. Vanesa SAIZ ECHEZARRET (Fonseca, Journal of Communication, 2023)
Scientific evidence has corroborated an underrepresentation of women in opinion journalism, in line with the pattern of exclusion of women’s voice in the public sphere. This paper explores this phenomenon from the perspective of local journalism: it quantifies the production of opinion texts during two weeks in 53 local media in Castilla-La Mancha, analyses the pieces (n=662) and observes the factors that indicate the imbalance through six interviews with women that collaborate in opinion content.